2007
DOI: 10.1074/jbc.m700050200
|View full text |Cite
|
Sign up to set email alerts
|

A Three Amino Acid Tail Following the TM4 Region of the N-Methyl-D-aspartate Receptor (NR) 2 Subunits Is Sufficient to Overcome Endoplasmic Reticulum Retention of NR1-1a Subunit

Abstract: The cytoplasmic C-terminal domains of NR2 subunits have been proposed to modulate the assembly and trafficking of NMDA receptors. However, questions remain concerning which domains in the C terminus of NR2 subunits control the assembly of receptor complexes and how the assembled complexes are selectively trafficked through the various cellular compartments such as endoplasmic reticulum (ER) to the cell surface. In the present study, we found that the three amino acid tail after the TM4 region of NR2 subunits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Whole-cell Patch Clamp Recording-The electrophysiological methods have been described previously (24). The extracellular recording solution contained 147 mM NaCl, 3 mM KCl, 10 mM HEPES, 8 mM glucose, 2 mM MgCl 2 (305 mosM, pH adjusted to 7.30 with NaOH).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-cell Patch Clamp Recording-The electrophysiological methods have been described previously (24). The extracellular recording solution contained 147 mM NaCl, 3 mM KCl, 10 mM HEPES, 8 mM glucose, 2 mM MgCl 2 (305 mosM, pH adjusted to 7.30 with NaOH).…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry-Surface-staining of HEK293 cells and cortical neurons was performed as described previously (24). Cortical neurons were plated on coverslips and transfected with the indicated plasmid on DIV 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface Immunostaining and Quantitative Analysis-These methods have been described previously (20,21). Cells were examined through a 60 ϫ 1.4 (numerical aperture) oil immersion objective on a FV1000 confocal laser scanning microscope equipped with imaging analysis software (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Second, using truncated and chimeric NMDA receptor subunits, we showed recently that M3 of both NR1 and NR2B possess ER retention signals and that these domains as well as M4 of NR1 are responsible for masking the ER retention signals in the M3 domains.10 Third, NR1/NR2 complexes can reach the cell surface membrane even when either one or both C-terminal regions are deleted five or six amino acid residues after M4.10 -12 However, full-length NR2B constructs lacking the HLFY motif, located one amino acid residue after the M4 domain, are not delivered to the surface membrane.6 Fourth, a later study showed that replacement of the HLFY motif with alanines in the NR2B subunit, truncated immediately after the mutated HLFY motif, does not affect the formation of functional channels. 13 Since this study also showed that at least three amino acid residues after NR2B M4 are necessary for surface trafficking of the receptors, this indicates that the NR2B M4 domain and surrounding segments are critical for correct assembly and formation of functional receptors. Finally, co-expression of the NR2 subunit truncated before M4 (NR2 preM4) with the full-length NR1 subunit fails to produce functional receptors.…”
mentioning
confidence: 99%